Worsening racial disparity in waitlist mortality for pediatric heart transplant candidates since the 2016 Pediatric Heart Allocation Policy revision. (3rd November 2022) - Wright, Lydia K.; Gajarski, Robert J.; Phelps, Christina; Hoffman, Timothy M.; Lytrivi, Irene D.; Magnetta, Defne A.; Shaw, Fawwaz R.; Thompson, Consuela; Weisert, Molly; Nandi, Deipanjan
Abstract: Background: The US Pediatric Heart Allocation Policy (PHAP) was revised in March 2016, with the goal of reducing waitlist mortality. We evaluated the hypothesis that these changes, which increased status exceptions, have worsened racial disparities in waitlist outcomes. Methods: Children in the Pediatric Heart Transplant Study database listed for first heart transplant from January 2012 – June 2020 were included and stratified by listing before (Era 1) or after (Era 2) the PHAP revision. Results: A total of 4, 089 children were listed during the study period. Compared with white children ( n  = 2648), non‐white children ( n  = 1441) were more likely to have an underlying diagnosis of cardiomyopathy in both eras. Waitlist mortality was similar in white and non‐white children in Era 1, but comparatively worse for non‐white children in Era 2. In multivariable analysis controlling for diagnosis, age, and severity markers, non‐white children had a significantly higher waitlist mortality only in Era 2 (Era 1: sHR 1.22 [95%CI 0.90 – 1.66] vs. Era 2: sHR 1.57 [95%CI 1.17 – 2.10]). Conclusions: Widening racial disparities in waitlist mortality may be an unintended consequence of the 2016 PHAP revision. Additional analyses may inform the degree to which this policy vs. unrelated changes in care differentially contribute to these disparities.